Electron density inside Enceladus plume inferred from plasma oscillations excited by dust impacts. Issue 5 (7th May 2014) - Ye, S.‐Y.; Gurnett, D. A.; Kurth, W. S.; Averkamp, T. F.; Morooka, M.; Sakai, S.; Wahlund, J.‐E.
Abstract Enceladus' southern plume is one of the major discoveries of the Cassini mission. The water neutrals and water ice particles (dust) ejected by the cryovolcanic activity populate Saturn's E ring and the neutral torus, and they interact with the plasma environment of Saturn's magnetosphere. The plasma neutrality inside Enceladus' plume has been shown by the Langmuir probe measurement to be modified by the presence of the dust particles. We present an independent method of determining the electron density inside the plume. Sometimes, after dust impacts, plasma oscillations (ringing) were detected by the Cassini Radio and Plasma Wave Science instrument. The frequencies of these oscillations have been shown to be consistent with the local plasma frequency, thus providing a measurement of the local electron density.